A rapid and reliable chromosome analysis method for products of conception using interphase nuclei. Issue 3 (24th March 2018) - Babu, Ramesh; Van Dyke, Daniel L.; Bhattacharya, Saurabh; Dev, Vaithilingam G.; Liu, Mingya; Kwon, Minjae; Gu, Guangyu; Koduru, Prasad; Rao, Nagesh; Williamson, Cynthia; Fuentes, Ernesto; Fuentes, Sarah; et al.
Abstract: Background: Karyotype determination has a central role in the genetic workup of pregnancy loss, as aneuploidy (trisomy and monosomy) and polyploidy (triploidy and tetraploidy) are the cause in at least 50% of first trimester, 25% of second trimester, and 11% of third trimester miscarriages. There are several limitations with the current approaches of obtaining a karyotype using traditional cytogenetics, fluorescence in situ hybridization with a limited number of probes, and chromosomal microarray. These include culture failure, incomplete results, lower sensitivity, and longer reporting time. Methods: To overcome current limitations, a novel molecular assay is developed with a Standard Resolution Interphase Chromosome Profiling probe set which is a variation of the recently developed High Resolution probe set. It generates a molecular karyotype that can detect all major changes commonly associated with pregnancy loss. Initial familiarization of signal patterns from the probe set was used, followed by validation of the method using 83 samples from miscarriages in a blind study from three different laboratories. Finally, the clinical utility of the method was tested on 291 clinical samples in two commercial reference laboratory settings on two different continents. Results: The new molecular approach not only identified all the chromosome changes observed by current methods, but also significantly improved abnormality detection by characterizing derivative chromosomes and finding subtle subtelomeric rearrangements, balanced and unbalanced. All Robertsonian translocations were also detected. The abnormality rate was 54% on clinical samples from commercial laboratory 1 and 63% from laboratory 2. Conclusion: The attributes of this method make it an ideal choice for the genetic workup of miscarriages, namely (1) near 100% successful results, (2) greater sensitivity than conventional chromosome analysis or FISH panels, (3) rapid reporting time, and (4) favorable comparisons with chromosomal microarray. Abstract : A novel, rapid, simple, comprehensive, and reliable interphase chromosome profiling method which detects all numerical and structural abnormalities including Robertsonian translocations in miscarriage samples.